14.7k views
2 votes
Solve.

−5x+6=−4(2x−1)


x=−14/3

x=−10/13

x=−2/3

User Briarheart
by
5.3k points

1 Answer

2 votes

Answer:

-2/3

Explanation:

First, distribute, -4(2x - 1) is -8x + 4. Next, do the opposite of the sign for the variable, since -8x can be written as - 8x, do the opposite sign, which is addition. -5 + 8 and -8 + 8. Add on both sides. Now you have 3x + 6 = 4. Then subtract 6 by 4. You'll get -2. The denominator is the number that has the variable. So now the equation will be 3x/3 = -2/3. You can turn -2/3 into a decimal, but it-s fine like that.

User Vordreller
by
4.7k points